Optimizing the Molecular Diagnosis of GALNS: Novel Methods to Define and Characterize Morquio—A Syndrome‐Associated Mutations. Issue 3 (13th March 2015) - Caciotti, Anna; Tonin, Rodolfo; Rigoldi, Miriam; Ferri, Lorenzo; Catarzi, Serena; Cavicchi, Catia; Procopio, Elena; Donati, Maria Alice; Ficcadenti, Anna; Fiumara, Agata; Barone, Rita; Garavelli, Livia; et al.
Abstract : We estabilished an array of techniques (QF‐PCR, CNV and CGH arrays): for the correct evaluation of MPS IVA patients' allelic composition, in order to achieve a diagnostic alogorithm to be used in the molecular analysis of MPS IVA syndrome: We characterised new identified mutations as a prerequisite to understanding the disease's natural progression in light of he incomming Enzyme Replacement Therapy for MPS IVA syndrome. ABSTRACT: Morquio A syndrome (MPS IVA) is a systemic lysosomal storage disorder caused by the deficiency of N‐acetylgalactosamine‐6‐sulfatase (GALNS), encoded by the GALNS gene. We studied 37 MPS IV A patients and defined genotype–phenotype correlations based on clinical data, biochemical assays, molecular analyses, and in silico structural analyses of associated mutations. We found that standard sequencing procedures, albeit identifying 14 novel small GALNS genetic lesions, failed to characterize the second disease‐causing mutation in the 16% of the patients' cohort. To address this drawback and uncover potential gross GALNS rearrangements, we developed molecular procedures (CNV [copy‐number variation] assays, QF‐PCRs [quantitative fluorescent‐PCRs]), endorsed by CGH‐arrays. Using this approach, we characterized two new large deletions and their corresponding breakpoints. Both deletions were heterozygous and included the first exon of the PIEZO1 gene, which is associated with dehydrated hereditary stomatocitosis, an autosomal‐dominant syndrome. In addition, we characterized the new GALNS intronic lesion c.245‐11C>G causing m‐RNA defects, although identified outside the GT/AG splice pair. We estimated the occurrence of the disease in the Italian population to be approximately 1:300, 000 live births and defined a molecular testing algorithm designed to help diagnosing MPS IVA and foreseeing disease progression.